2017
DOI: 10.3141/2631-17
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Illinois Flexibility Index Test to Mixture Design Factors

Abstract: The semicircular bend test was recently modified to develop the Illinois flexibility index test (I-FIT). The I-FIT test quantifies the cracking resistance of asphalt mixtures by using the flexibility index (FI), which includes the fracture energy and postpeak behavior of a mixture. This paper presents results from testing asphalt mixtures in Wisconsin. A statistical analysis approach was chosen for this study, in which the I-FIT procedure was used to differentiate between mixtures on the basis of changes in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The fracture resistance, and subsequently the cracking potential of mixtures, was evaluated based on the flexibility index (FI). From the load and displacement history recorded during the SCB tests, the following fracture parameters were extracted to calculate the FI as follows [33,34]:…”
Section: Test Methods For Characterizing Asphalt Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture resistance, and subsequently the cracking potential of mixtures, was evaluated based on the flexibility index (FI). From the load and displacement history recorded during the SCB tests, the following fracture parameters were extracted to calculate the FI as follows [33,34]:…”
Section: Test Methods For Characterizing Asphalt Mixturesmentioning
confidence: 99%
“…The fracture resistance, and subsequently the cracking potential of mixtures, was evaluated based on the flexibility index (FI). From the load and displacement history recorded during the SCB tests, the following fracture parameters were extracted to calculate the FI as follows [ 33 , 34 ]: G f = W f / area, FI = G f × 0.01/ |m|, where W f = work of fracture (Joules); area = ligament area (the product of the ligament length and the thickness of the specimen); G f = fracture energy (Joules / m 2 ); and m = post-peak slope (kN/mm).…”
Section: Test Methods For Characterizing Asphalt Mixturesmentioning
confidence: 99%
“…In some studies, the FI obtained was found to yield reasonable correlations with field performance of pavements ( 21 ). Others provided both positive and negative conclusions regarding the capability of this test in discriminating mixtures ( 22 , 23 ). In a more recent study, FI was found to be highly variable and was not sensitive to the presence and type of polymer modifiers ( 24 ).…”
Section: Test Methodsmentioning
confidence: 99%
“…The detailed definition and calculation of each parameter can be found in reference [14]. It was reported that fracture energy alone was insufficient to discriminate among mixture design factors while FI is a valuable parameter in ranking the cracking performance of asphalt mixture [15]. Therefore, in this study, FI was used to compare the thermal cracking resistance of asphalt mixture with/without lignin.…”
Section: Thermal Cracking Resistancementioning
confidence: 99%